ANALISIS KINERJA KOPERASI UNIT DESA MAKARYO MINO DALAM USAHA PEMBERDAYAAN MASYARAKAT NELAYAN DI KOTA PEKALONGAN - Adam, Brefin Mushtaf; Rosyid, Abdul; Triarso, Imam (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Cooperative is a business enterprise consisting of the person or legal entity with bases cooperative activities based on the principle of cooperation as well as economic movement is based on the principle of the family. The purpose of this study to know the effort units in a managed fishery KUD Makaryo Mino, analyzing the performance of KUD Makaryo Mino in its effort units in the areas of fisheries and other programs related to the fishing community empowerment efforts and empowerment strategy fishing communities. The method used in this research was descriptive method is done by direct observation in the field. The sampling method used two methods are respondents used quota sampling method to measure subscriber satisfaction by number of respondents 30 people, and a purposive sampling method to make by 5 renponden strategy. Analytical methods used Balanced Scorecard (BSC) and the determination of strategies used SWOT analysis. The result shows that KUD Makaryo Mino was cooperative fisheries that concerns in Ice Production, Trading, SPBB, and Fish basket renting. KUD Makaryo Mino not only the supply of ship supplies but also the provision of loan capital and social programs in cooperation with the government of Pekalongan in fishermen's welfare program. Performance assessment results Makaryo Mino Village Cooperatives in 2011 by reference to the State Minister of Cooperatives and Small and Medium Enterprises Republic of Indonesia 06/Per/M.KUKM/V/2006 has a value of 81.5% yield performance can be declared successful performance, and appropriate responses to respondents in 2010 received 80.14% performance results can be declared a success and in 2011 amounted to 85.24 % can be expressed very successful. Alternative solutions in order to achieve the empowerment of fishing communities according SWOT analysis application strategy results obtained SO (Strength-opportunity) was working with the city government to provide facilities and infrastructure supporting an easy fishing, the price is cheap and the search seeking alternative employment opportunities in the famine, make a purchase at a price above the catch-basket fish basket panawaran and middlemen who are buying low, coordinating with the fishing port and municipal governments to set the price of the fish auction market, and Creating breakthrough new business that the provision of business information services PPDPI (fishing regional forecast map).